Evaluation of the Effects of Novel Educational Methods on Learning and Retention of the Course of Hereditary Diseases and Genetic Counseling - Behnaz Hatef; Zahra Mohamadi; Nejleh Rajabi; Ehsan Saburi (Kerman University of Medical Sciences, 2016)
Background & Objective: Due to the disadvantages of teaching through lectures the need for their replacement with active and collaborative learning methods is strongly felt Students of public health due to employment in the health network have an important role in screening for genetic disorders This study aimed to change teaching methods to increase retention of practical contents in the minds of undergraduate students of public health after graduation Methods: This quasiexperimental study was conducted on 20 public health students of Zanjan University of Medical Sciences Iran The course of hereditary diseases and genetic counseling was taught with a new method that combines traditional and modern (the use of blogs PowerPoint discussion in small groups on clinical issues and developmental quizzes) teaching methods A year after the final exam an exam and survey were held The results of the survey and students grades were analyzed using paired ttest in SPSS software Results: Average scores of the final exam and 1year reexamination were 1725 and 1110 respectively and the difference was statistically significant (P = 0004) However the students stated that they remembered more than 86% of the topics covered in class to some extent Among the students 45% and 14% believed this to be due to developmental quizzes and problembased learning respectively No significant difference was observed in the components of students satisfaction from teaching between the two mentioned time periods (P = 0196) Conclusion: Continuous developmental quizzes due to repetition of course content at short intervals and problembased learning in small groups due to promoting dynamism of mind and increasing motivation to remember because of participation in debates cause the students to remember more and for a longer period